2014
DOI: 10.1097/jom.0000000000000000
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Selective Participation in a Physical Activity Intervention on the Generalizability of Findings

Abstract: Selective participation may reduce the potential benefit of interventions and limit generalizability of findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In studies among adults, non-participation in studies about respiratory conditions is associated with higher prevalence of smoking 13 14 33 and lower SES. 16 Further, non-participation in an alcohol use prevention study among teenagers was related to lower parental socioeconomic level. 34 However, little is known about non-participation in smoking prevention programmes among teenagers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies among adults, non-participation in studies about respiratory conditions is associated with higher prevalence of smoking 13 14 33 and lower SES. 16 Further, non-participation in an alcohol use prevention study among teenagers was related to lower parental socioeconomic level. 34 However, little is known about non-participation in smoking prevention programmes among teenagers.…”
Section: Discussionmentioning
confidence: 99%
“…Among adults, it is known that the prevalence of smokers is higher among non-participants in questionnaire surveys regarding respiratory conditions 13–15 and in health promotion interventions. 16 However, few studies have reported on factors related to non-participation in tobacco intervention among teenagers. One available study showed that non-participation in a family-directed tobacco and alcohol prevention programme was related to male sex, lower parental education and parental smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Good quality recruitment strategies into WHP programmes also play an important role so that there is broad employee participation. Programmes need to be available and accessible to participants [ 17 ], and attract people at risk of poor health rather than just selective participation from the ‘worried well’ [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, previous research, including our own for pH@W 40 has shown that employees with suboptimal health-related behaviors are less likely to engage in WHP activities, even though the greatest health gains might be achieved and observed in these groups. 74,75 Programs take a number of years to be accepted, utilised, and become functionally operational before the desired outcomes may be achieved. 6 Over a time frame of three years, our study shows evidence of interim health-related outcomes for the implementation approach used for pH@W, and no shift in employee health-related behaviors or BMI.…”
Section: Discussionmentioning
confidence: 99%